Widely used pharmaceuticals present in the environment revealed as in vitro antagonists for human estrogen and androgen receptors - Ezechiáš, Martin; Janochová, Jana; Filipová, Alena; Křesinová, Zdena; Cajthaml, Tomáš (Chemosphere, 2016)
A considerable amount of scientific evidence indicates that a number of pharmaceuticals that could be detected in the environment can contribute towards the development of problems associated with human reproductive systems, as well as those of wildlife. We investigated the estrogenic and androgenic effects of select pharmaceuticals with high production volume and environmental relevance. We examined the receptor-binding activities of these pharmaceuticals in the T47D human cell line using altered secretion of cytokine CXCL12. Functional yeast-luciferase reporter gene assays were also employed to confirm the mechanism of receptor binding by estrogen and androgen. Non-steroidal anti-inflammatory drugs, namely ibuprofen, diclofenac and antiarrhythmic agent amiodarone showed strong anti-estrogenic effects in the T47D cell line. In the yeast-luciferase assay, these anti-inflammatory drugs also demonstrated anti-estrogenic potency and inhibited the E2 response in a concentration-dependent manner. Amiodarone did not exhibit any response in the yeast-luciferase assay; therefore, the endocrine disruption presumably occurred at a different level without directly involving the receptor. All the anti-inflammatory drugs considered in this study, including ketoprofen, naproxen and clofibrate, exhibited a dose-dependent antagonism towards the androgen receptor in the yeast-luciferase assays. Several other drugs, including the stimulant caffeine, did not show any response in the tests that were employed. A risk assessment analysis using 'Hazard Quotient' suggested a potential risk, especially in the cases of ibuprofen, ketoprofen, diclofenac and clofibrate. The results reveal the intrinsic endocrine disrupting nature of several pharmaceuticals and thus could contribute towards explaining a number of adverse health effects on humans and wildlife.
Keywords: biotest; Receptors, Estrogen; Endocrine Disruptors; antiflogistika nesteroidní; Chemokine CXCL12; antagonisté estrogenu; vztah mezi dávkou a účinkem léčiva; Androgens; chemické látky znečišťující vodu; Cell Line, Tumor; luciferasy; Water Pollutants, Chemical; Saccharomyces cerevisiae; endokrinní disruptory; reportérové geny; lidé; receptory pro estrogeny; Pharmaceutical Preparations; léčivé přípravky; Anti-Inflammatory Agents, Non-Steroidal; Estrogen Antagonists; Dose-Response Relationship, Drug; Biological Assay; Luciferases; Receptors, Androgen; Estradiol; Genes, Reporter; androgenní receptory; androgeny; nádorové buněčné linie; chemokin CXCL12; estradiol; Humans